Learning to adapt: managing forests together in Indonesia - Kusumanto, T.; Yuliani, L.; Macoun, P.; Indriatmoko, Y.; Adnan, H. (Center for International Forestry Research, 2005)
There is an increasing need to enhance the quality of forest management in many places around the world. This need often arises from disagreements among interest groups using the same forestland and forest resources. This situation also holds true for Indonesia. Yet while it is generally agreed that the problem should be tackled through better collaboration among competing groups, there are many questions about how to go about it in practice. This book tries to answer some of them. It is about a learning-based approach to collaboration, called Adaptive Collaborative Management (ACM). It draws on the experience of the Center for International Forestry Research (CIFOR) in researching and applying ACM in two sites in Indonesia: Sumatra and Kalimantan. It presents the way in which a team of action researchers assisted local groups and institutions in jointly addressing local resource problems and the outcomes and implications for wider application in the country. The book aims to support community workers, field-based staff of organisations like non-governmental organisations (NGOs), government extension workers and project staff, and trainers. It can be used as a reference, as a tool to facilitate local action, or simply as an account of experiences in applying a learning-based approach to forest management. The book can also be used as a basis for thinking about new methods, tools or concepts related to forests and for linking these to practice.